Oral culture and Catholicism in early modern England - Shell, Alison (Cambridge University Press, 2007)
After the Reformation, England's Catholics were marginalised and excluded from using printed media for propagandist ends. Instead, they turned to oral media, such as ballads and stories, to plead their case and maintain contact with their community. Building on the growing interest in Catholic literature which has developed in early modern studies, Alison Shell examines the relationship between Catholicism and oral culture from the mid-sixteenth to the eighteenth centuries. In order to recover the textual traces of this minority culture, she expands canonical boundaries, looking at anecdotes, spells and popular verse alongside more conventionally literary material. In her archival research she uncovers many important manuscript sources. This book is an important contribution to the rediscovery of the writings and culture of the Catholic community and will be of great interest to scholars of early modern literature, history and theology.